The Influence of Digital Transformation on the Performance of Mayapada Hospital Bandung Through Innovation as a Mediator - Ryan Adinta Asrul; Nurvita Trianasari (Eduvest - Journal of Universal Studies, 2026)
This study aimed to analyze the impact of digital transformation technology on hospital performance in Bandung City. In the current digital era, the healthcare sector is undergoing significant changes through the integration of information and communication technology (ICT). Hospitals are increasingly adopting digital technologies to improve operational efficiency and enhance healthcare service quality. This research employed a quantitative approach, surveying 50 hospitals in Bandung. Data were collected through questionnaires designed to measure technology adoption levels, operational efficiency, and patient satisfaction. The analysis results revealed a significant positive relationship between technology adoption levels and improvements in hospital performance. Specifically, higher levels of technology adoption were associated with enhanced service efficiency, reduced patient waiting times, and increased patient satisfaction. Hospitals that effectively implemented digital solutions streamlined operations, improved care quality, and met growing patient expectations for convenience and satisfaction. These findings highlight the importance of digital transformation for hospital management in Bandung and offer valuable insights into how healthcare institutions can leverage technology to enhance operations. Hospital managers can use these insights to plan and implement effective digital strategies, ultimately improving the overall quality and efficiency of healthcare services provided to the community.